Upaya Deradikalisme Dalam Lingkungan Sekolah Dan Implikasinya Terhadap Ketahanan Ideologi - Jagad, Moh. Alief Bias; Saputri, Oktavia Wahyuni (EDUCOUNS GUIDANCE: Journal of Educational and Counseling Guidance, 2024)
This study aims to demonstrate that deradicalism in the environment will affect the resilience of students' ideologies in the current era. Radicalism is a problem that occurs in the world of education. Schools in Indonesia in recent years have become targets of radicalism. The notion of radicalism that dominates the ideology of students is a special concern for school components. Thus, it is necessary to take serious action to counteract radicalism in the school environment. This research is descriptive qualitative research accompanied by analysis with the support of secondary sources. The results of this study indicate that the strength of this ideology can be seen in the views and attitudes of activists who tend to be exclusive, placing pluralism as an understanding that must be avoided. This tendency continues to strengthen in line with the entry of the radical Islamic group cadre movement into schools. In his study of deradicalism, which contains characters that refer to Pancasila, it has implications for the ideological resilience of students, where this deradicalization effort directs students to become individuals with character in accordance with Pancasila, which is summarized in a Pancasila Student Profile.